Summoning the dead : essays on Ron Rash - Wilhelm, Randall; Vernon, Zackary; Morgan, Robert (The University of South Carolina Press, 2018)
The first book-length examination of the award-winning author of poetry and fiction firmly rooted in Appalachia.